Two human MYD88 variants, S34Y and R98C, interfere with MyD88-IRAK4-myddosome assembly. - George, J; Motshwene, P; Wang, H; Kubarenko, A; Rautanen, A; Mills, T; Hill, A; Gay, N; Weber, A (2011)
Innate immune receptors detect microbial pathogens and subsequently activate adaptive immune responses to combat pathogen invasion. MyD88 is a key adaptor molecule in both Toll-like receptor (TLR) and IL-1 receptor superfamily signaling pathways. This is illustrated by the fact that human individuals carrying rare, naturally occurring MYD88 point mutations suffer from reoccurring life-threatening infections. Here we analyzed the functional properties of six reported non-synonymous single nucleotide polymorphisms of MYD88 in an in vitro cellular system. Two variants found in the MyD88 death domain, S34Y and R98C, showed severely reduced NF-κB activation due to reduced homo-oligomerization and IRAK4 interaction. Structural modeling highlights Ser-34 and Arg-98 as residues important for the assembly of the Myddosome, a death domain (DD) post-receptor complex involving the DD of MyD88, IRAK4, and IRAK2 or IRAK1. Using S34Y and R98C as functional probes, our data show that MyD88 homo-oligomerization and IRAK4 interaction is modulated by the MyD88 TIR and IRAK4 kinase domain, demonstrating the functional importance of non-DD regions not observed in a recent Myddosome crystal structure. The differential interference of S34Y and R98C with some (IL-1 receptor, TLR2, TLR4, TLR5, and TLR7) but not all (TLR9) MyD88-dependent signaling pathways also suggests that receptor specificities exist at the level of the Myddosome. Given their detrimental effect on signaling, it is not surprising that our epidemiological analysis in several case-control studies confirms that S34Y and R98C are rare variants that may drastically contribute to susceptibility to infection in only few individuals.